Alkyl chain length-dependent surface reaction of dodecahydro-N-alkylcarbazoles on Pt model catalysts - Gleichweit, Christoph; Amende, Maximilian; Bauer, Udo; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Müller, Michael; Koch, Marcus; Bachmann, Philipp; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Chemical Physics, 2014)
The concept of liquid organic hydrogen carriers (LOHC) holds the potential for large scale chemical storage of hydrogen at ambient conditions. Herein, we compare the dehydrogenation and decomposition of three alkylated carbazole-based LOHCs, dodecahydro-N-ethylcarbazole (H-NEC), dodecahydro-N- propylcarbazole (H-NPC), and dodecahydro-N-butylcarbazole (H -NBC), on Pt(111) and on AlO-supported Pt nanoparticles. We follow the thermal evolution of these systems quantitatively by in situ high-resolution X-ray photoelectron spectroscopy. We show that on Pt(111) the relevant reaction steps are not affected by the different alkyl substituents: for all LOHCs, stepwise dehydrogenation to NEC, NPC, and NBC is followed by cleavage of the C-N bond of the alkyl chain starting at 380-390 K. On Pt/AlO, we discern dealkylation on defect sites already at 350 K, and on ordered, (111)-like facets at 390 K. The dealkylation process at the defects is most pronounced for NEC and least pronounced for NBC. © 2014 AIP Publishing LLC.

Hydrogen Storage: Thermochemical Studies of N-Alkylcarbazoles and Their Derivatives as a Potential Liquid Organic Hydrogen Carriers - Emel'Yanenko, Vladimir N.; Varfolomeev, Mikhail A.; Verevkin, Sergey P.; Stark, Katharina; Müller, Karsten; Müller, Michael; Bösmann, Andreas; Wasserscheid, Peter; Arlt, Wolfgang (Journal of Physical Chemistry C, 2015)
Although N-ethylcarbazole is considered as a most promising potential liquid organic hydrogen carriers (LOHC) substance, a major drawback for stationary and particularly mobile applications is its high melting point of 343 K. Study of other possible N-alkylcarbazole-derivatives having lower melting points but keeping a high storage density is of practical importance. This contribution presents thermochemical properties (enthalpy of formation, enthalpy of vaporization, enthalpy of sublimation, and fusion enthalpy) for N-alkylcarbazoles (with alkyl = isopropyl, n-propyl, and n-butyl) derived from experiments in order to investigate the applicability of the carbazole derivatives as potential LOHCs. Additionally, high-level quantum chemical calculations were applied to determine molar enthalpies of formation of the gaseous carbazole derivatives and thus validated the experimental findings. Using a combination of the quantum-chemical calculations with vaporization enthalpy data measured in this work, the standard molar liquid phase enthalpies of formation were derived for alkylcarbazole derivatives. Results of this study were applied for thermodynamic analysis of the liquid-phase reversible hydrogenation/dehydrogenation processes with N-alkylcarbazoles.

Measurement of Hydrogen Solubility in Potential Liquid Organic Hydrogen Carriers - Aslam, Rabya; Müller, Karsten; Müller, Michael; Koch, Marcus; Wasserscheid, Peter; Arlt, Wolfgang (Journal of Chemical and Engineering Data, 2016)
Liquid organic hydrogen carriers (LOHC) are potential compounds that can facilitate chemical energy storage and hydrogen logistics using reversible hydrogenation. For the process development, the physical solubility of hydrogen in potential LOHCs is required. In this work, solubility of hydrogen in the potential LOHC systems toluene/methylcyclohexane, N-ethylcarbazole/perhydro-N-ethylcarbazole, and dibenzyltoluene/perhydrodibenzyltoluene was measured using the static isochoric saturation method. The data were measured at low pressures up to 10 bar within the temperature range of (293 to 373) K. Hydrogen solubility in hydrogenated forms of the LOHCs was found to be higher compared to the dehydrogenated forms. Solubility in all substances increased with increasing temperature within the whole temperature range under consideration. The temperature dependency of the Henry coefficient of hydrogen in the solvents was correlated using the Benson and Krause correlation.